What Shapes the Perceived Quality of Local Government Financial Reports? Evidence from the Special Region of Yogyakarta - M. Arsyadi Ridha; Yoananda Aurora Salsabila; Sofyan Hadinata (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This study aims to examine the key factors influencing the perceived quality of local government financial reports, focusing on internal stakeholder perceptions of decision usefulness, public accountability, and transparency. Method: A quantitative research approach was employed using a survey method. The population comprised all local government units (Organisasi Perangkat Daerah or OPD) in the Special Region of Yogyakarta, with purposive judgment sampling used to select relevant departments and agencies. The respondents were finance and accounting personnel within each sampled OPD. Data were collected through structured questionnaires and analyzed using WarpPLS 7.0 to assess the measurement model and test the proposed hypotheses via structural equation modeling (SEM). Findings: The results reveal that perceived decision usefulness, accountability, and transparency each have a significant and positive effect on the perceived quality of financial reports. These findings suggest that internal users’ judgments of report quality are strongly influenced by how well financial information supports managerial decisions, fulfills accountability expectations, and communicates financial realities transparently. Novelty: This study contributes to the public sector accounting literature by integrating three theoretical perspectives, decision-usefulness theory, public accountability theory, and transparency theory, to explain variation in perceived financial reporting quality. By focusing on the perceptions of internal stakeholders in local government, the study offers a contextualized understanding of how technical and normative dimensions of reporting shape quality assessments in a decentralized public finance environment.